2022
DOI: 10.1177/00031224221076487
|View full text |Cite
|
Sign up to set email alerts
|

From Bat Mitzvah to the Bar: Religious Habitus, Self-Concept, and Women’s Educational Outcomes

Abstract: This study considers the role of religious habitus and self-concept in educational stratification. We follow 3,238 adolescents for 13 years by linking the National Study of Youth and Religion to the National Student Clearinghouse. Survey data reveal that girls with a Jewish upbringing have two distinct postsecondary patterns compared to girls with a non-Jewish upbringing, even after controlling for social origins: (1) they are 23 percentage points more likely to graduate college, and (2) they graduate from muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Given the increasingly diverse landscape of the United States-and the outsized role that religious institutions play for immigrants-it is particularly important to examine whether religion matters for the educational journeys of students who identify as Muslim or Catholic Latinos (Guhin 2019). Accounting for gender differences in different religious traditions in an especially fruitful line of research since religion and gender ideologies are intertwined (Horwitz et al 2019). It is also important for future research to consider variation within religious groups.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasingly diverse landscape of the United States-and the outsized role that religious institutions play for immigrants-it is particularly important to examine whether religion matters for the educational journeys of students who identify as Muslim or Catholic Latinos (Guhin 2019). Accounting for gender differences in different religious traditions in an especially fruitful line of research since religion and gender ideologies are intertwined (Horwitz et al 2019). It is also important for future research to consider variation within religious groups.…”
Section: Discussionmentioning
confidence: 99%
“…But they are also more progressive, and minoritized religious groups are some of the most liberal in the United States, and past research has demonstrated differing patterns on politicized factors including women's opportunities and, importantly for this study, social attitudes and political ideology among minoritized religious groups (Horwitz et al. 2022; O'Brien and Abdelhadi 2020; Wilde 2018). Such religions—with their more fervent beliefs and greater commitment to absolute truth claims than groups like Unitarian Universalists—could also yield stronger exposure effects.…”
Section: Expectationsmentioning
confidence: 88%
“…For example, Horwitz et al. (2021) found that children, and especially girls, raised in a non‐Orthodox Jewish habitus tend to get more education and attend better schools than other children from a comparable social location.…”
Section: Question 7: How Does Religion Shape Behaviors and Life Outco...mentioning
confidence: 99%
“…Nevertheless, more progressive forms of religious subculture can actually boost women's and to a lesser extent men's career trajectories. For example, Horwitz et al (2021) found that children, and especially girls, raised in a non-Orthodox Jewish habitus tend to get more education and attend better schools than other children from a comparable social location.…”
Section: Work Earnings and Educationmentioning
confidence: 99%